Tata Ruang dalam Gereja yang Secara Liturgis Menarasikan Karya Allah - Rasid Rachman (STFT Jakarta, Indonesia, 2021)
The explanation of the church building as a liturgical space in this article will focus on two things. First, the area that separates the sacred from the secular world. The separated place points towards the meaning of the church that reveals God‘s presence in the world. The church is not just alive but also gives meaning to the whole life of the entire creation. Second, the celebration room that narrates God‘s works in history. As a liturgical area, the church building uses several metaphors to tell about God‘s works, for example, the gate of heaven, the pregnant mother, and the sailing ship. This article argues that the interior of the liturgical space narrates the church‘s view on God and God‘s creation. Further, this article emphasizes for the importance of the liturgical space as a reflection of the church theology by using the ritual, theological, and anthropological views of the church‘s interior space.